Comparison of risk index estimating methods on the Polish financial market - Krzysztof Janas (e-Finanse: Financial Internet Quarterly, 2018)
The purpose of this paper is to determine a practical approach of calculation of the systematic risk of companies in line with the CAPM model. By performing an analysis of the methodology used in practice of determining the beta and review of the literature on the subject the accounting rules that make the best possible impact on the change in the level of risk index are determined. In this work on the Polish financial market are also carried out simulations showing the impact of the change in assumptions on the final amount of beta. Based on the empirical results there is a recommendation formulated as to what method should determine beta for public companies using the CAPM model. These boundary conditions are also possible implementations of the proposed approach and possible desirable solutions, if minimum boundary conditions are not met. The defined scope for the use of the recommended method of calculating the risk index allows us to reduce the error probability of over-or underestimation of the value of the index.
Keywords: G12; C33; 330; valuation; systematic risk; cost of capital; bankruptcy forecasting